Potensi Serbuk Kayu Ulin dan Serbuk Bambu Sebagai Aplikasi Papan Partikel Ramah Lingkungan - Review - Laksono, Andromeda Dwi; Rozikin, Muhammad Nurhidayatur; Safitri Pattara, Nur Aini; Cahyadi, Ifdil (Jurnal Rekayasa Mesin, 2021)
The wood and bamboo waste from the exploitation and industry are still not fully utilized where they are now being used as raw material for particleboard. The purpose of this narrative review is to find out the concept of particleboard, the mechanism of particleboard, and the potential for wood and bamboo powder in particleboard applications. The method of creating particleboard was using dehydrated sawdust and bamboo then pouring the powder with adhesive. In this narrative review, there are several types of adhesives which are Polyurethane Resin, Phenol-Formaldehyde (PF), Epoxy, Polystyrene Based Resin (PBR), and Unsaturated Polyester (UP). After molding powder and adhesive mixture, it was hot-pressed to make a particleboard product. Finally, the mixture was tested for the physical and mechanical properties of particleboard products based on Indonesian National Standard. The physical and mechanical properties are increases by particleboard with a proportion of 75%-100% teak wood (T. Grandis) and 25%-50% bamboo. It's known that ironwood has characteristics close to that of the teak species. Therefore, the ironwood and bamboo sawdust has the potential to be used as raw material for particleboard. And the recommended method based on the type of adhesive used is UP.